Optimization of the amino functionalization of magnetic nanoparticles for Use in MNP-CLEA technology - Khatun, Hanufa; Yusof, Faridah; Mohamed Azmin, Nor Fadhillah (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The purpose of this research is to optimize the functionalization process of magnetic iron oxide nanoparticles for CLEA immobilization to enzymes, as a solution to the present challenges of CLEA technology such as clumping. A co-precipitation method was used to synthesize the magnetic nanoparticles (MNP), in which ferric chloride (FeCl3.6H2O) and ferrous sulfate (FeSO4.7H2O) were used to provide Fe3+ and Fe2+ ions. Ammonium hydroxide (NH4OH) was used as the precipitator of the MNPs. For the MNPs to be immobilized with proteins through cross-linking, they had to be functionalized with amino groups by 3-aminopropyltrimetoxysilane (APTES), through a silanization reaction. Silicon ions in APTES connected with oxygen in the iron oxide particles, thus forming a connection between the nanoparticles and the amino groups inside APTES. The functionalization of the MNPs with amino groups was optimized using One Factor at a Time (OFAT), with APTES as the significant parameter. The percentage of BSA immobilized on the functionalized nanoparticles was used to determine the ability of the functionalized MNPs to immobilize proteins for each possible optimal run. The optimum concentration for APTES in the amino functionalization of magnetic nanoparticles was found to be 2.145 M.